Effects of Mesoscale Eddies in the Northern South China Sea on Phytoplankton Size and Physiological Status - Jinzheng Chen; Fenfen Liu (Remote Sensing, 2022)
Mesoscale eddies have essential effects on the distribution of the different sizes of phytoplankton and the status of phytoplankton physiology. The impact of mesoscale eddies on phytoplankton size and physiological level in the northern South China Sea is analyzed based on satellite data and HYCOM-simulated results from 2003 to 2018. The results show that there are higher nanophytoplankton levels for high and low nonlinearity in the center of cyclonic eddies. At the same time, the growth rate of phytoplankton increased, and the assimilation of phytoplankton decreased. Moreover, in the center of anticyclonic eddies, a lower nanophytoplankton level is observed in both high and low nonlinearity. At the same time, the growth rate of phytoplankton decreased, and the assimilation of phytoplankton increased. In addition, there is a higher nanophytoplankton level in the mode-water eddy, while the growth rate of phytoplankton is increased, and the assimilation of phytoplankton is decreased.